Resistances, Relationships, and True Community: Sikhs (Asian-Canadians?) in BC’s Lower Mainland - Kaur Sandhra, Sharanjit (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2024)
This article looks at the experience of Sikh Canadians in British Columbia’s lower mainland. First, I offer a critique of how and where their stories and histories fit within broader academic explorations of “Asian Canadian” themes. I then examine erasures in the archive connected to the building of the oldest still-standing gurdwara in the western hemisphere, the Gur Sikh Temple. The building of this Sikh sacred space offers several markers of resistance, including those that focus on relationships between different Asian Canadian communities as opposed to seeing resistance in relationship to whiteness only.